UKRAINE – USA TAX AGREEMENT AS A TOOL OF TAX LOAD OPTIMIZATION: CONSULTATIVE FRAMEWORK TO AVOID DOUBLE TAXATION - SHYROBOKOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The Convention between the Government of Ukraine and the Government of the United States of America for the Avoidance of Double Taxation and the Prevention of Tax Evasion with Respect to Taxes on Income and Capital serves as a regulatory basis for reducing the tax burden on cross-border transactions. However, in practice, the implementation of the provisions of the Convention is accompanied by significant difficulties. The purpose of the study is to substantiate the need to implement and form an advisory framework for optimizing the tax burden in accordance with the Ukraine-USA Convention for the Avoidance of Double Taxation. To achieve this goal, the following tasks have been identified: to analyze the key provisions of the Convention and modern methods of avoiding double taxation; to outline the shortcomings of the existing practice of tax consulting in Ukraine; to develop an algorithm (framework) of consulting for optimizing taxation. As the analysis of world tax practice shows, currently there are the following methods of avoiding double taxation: tax treaties, offsetting of tax paid abroad, automatic exchange of information on financial accounts, minimization of aggressive tax planning, exemption of income from taxation, implementation of a global minimum tax. Bilateral treaties are an established world practice within the framework of the modern international taxation system. Analysis of the Ukraine-USA Convention made it possible to identify its inconsistency with the latest tax trends and problems in practical implementation. Problems of tax consulting in Ukraine were also identified, in particular the underdeveloped market of international tax consulting. A single framework covering all stages of tax consulting and an algorithm for preparing recommendations for taxpayers under the Ukraine-USA tax treaty can contribute to solving the problems. Based on the results of the study, conclusions were drawn and directions for further research were identified.
Keywords: tax consulting; double taxation; Ukraine-USA Convention; tax agreement; advisory framework